Probabilistic criterion for Gausian equivalent linearization - Anh, N. D.; Schiehlen, W. (Vietnam Journal of Mechanics, 1996)
Within the scope of Gaussian equivalent linearization, a new probabilistic criterion for determining the coefficients of the linearized equivalent equation is proposed to treat stationary response of non-linear systems under zero mean Gaussian ro.nd.om excitation. Application to the Duffing oscillate subjected to white noise is presented that shows significant improvement over corresponding accuracy of the classical Gaussian equivalent linearization for both weak and strong non-linear.